Tingkat Pendidikan Keluarga Tidak Berasosiasi dengan Risiko Tempat Perkembangbiakan Potensial Nyamuk Aedes aegypti : Kasus di Kota Serang - Mutiara Widawati; Tri Wahono; Yuneu Yuliasih (ASPIRATOR - Journal of Vector-borne Disease Studies, 2016)
Habitat and human behavioural change is one of mosquito control effort that involves community participation in its process. This study aims to determine whether the level of education in a family influence its home into an Aedes aegypti’s breeding place in Serang. The study design was cross-sectional, with field observations and interviews in it. We use husband and wife or an adult for our samples to be interviewed. To determine the risk of mosquito larvae breeding, in each house we used three classifications of Maya Index determined from the existence of controllable and disposable water containers. The results showed that of the entire container found, 98.7% arecontrollablecontainers (94.7% positive larvae), and the remaining 1.3% are disposable containers (72.7% positive larvae). Based on the results of Chi-square analysis, it is known that education level had no effect on the risk of mosquito breeding places of Ae.aegypti in the city of Serang. We conclude that the level of education of parents in a home does not affect the presence of larval breeding sites of Ae.aegypti in Serang city. It is recommended that the local government intervene the society’s knowledge that focuses on mosquito breeding place controls, in order to avoid the emergence of new mosquitoes breeding place.